High adsorption of methylene blue by activated carbon prepared from phosphoric acid treated eucalyptus residue - Han, Qiaoning; Wang, Jing; Goodman, Bernard A.; Xie, Junkang; Liu, Zuguang (Powder technology, 2020)
Activated carbon with large specific surface area (1545 m2·g−1) and total acid density (2.47 mmol·g−1) was prepared by thermal activation of phosphoric acid treated eucalyptus residue, and was successfully used for simulated dye wastewater treatment where it showed high methylene blue (MB) adsorption capacity (977 mg·g−1). The textural properties and acidic functional groups of the activated carbon could be adjusted and controlled by phosphoric acid/eucalyptus residue mass ratios and activation temperature. Moreover, acidic functional groups could enhance MB adsorption by converting the adsorption pattern from planar to side adsorption with a decrease in activation temperature. The adsorption process was well described by the pseudo-second order kinetics and the Langmuir isotherm model, and it was demonstrated that intra-particle diffusion involved multi-linear stages. These findings provide important insights for the efficient treatment of dye wastewater on an industrial scale using waste eucalyptus residue. [Display omitted] •H3PO4 activated carbon was developed from waste eucalyptus residues.•The activated carbon has large specific surface area, high total acid density and yield.•The activated carbon has excellent adsorption performance to methylene blue.•The specific surface area and acidic functional groups play important role in adsorption capacity.•The adsorption pattern of methylene blue changed with the increase of acidic functional groups.